Foreign Investment Attraction in Yogyakarta: Gempa Bumi 27 Mei 2006 - Ekowati, Dhiana (Accounting, 2010)
This study aims to identify the variables inhibitors and attraction of foreign investors in investing in Yogyakarta. In addition, also observed how much influence the perspective of foreign investors towards the Yogyakarta earthquake-prone. This research was conducted in the Yogyakarta area on May October 2009. The analytical tool used is the method of Analytical Hierarchy Process (AHP) and regression analysis. AHP results found that the factors that the main attraction of foreign investment in Yogyakarta is the cultural factor and tourism, with the weight (20.4): The results found that the factors of culture and tourism became the main consideration for foreign investors wishing to invest in Yogyakarta, by weight 20.4%. The second factor that affects the attraction of foreign investment in Yogyakarta is the institutional factor with a weight factor of 20.2% followed by social security politics by weight 17.1%, with a weighting factor of 13.3% of infrastructure, regional economic factors by weight 12.5% , weighting factor of employment with 9.3%, and the factors that have the lowest weight is the geographic location and potential for disaster with a weighting of 7.2%. Through regression found that the geographical factor and the potential for disaster in a negative effect on foreign investment attraction with a coefficient of 0.281. Keywords: Attraction of Foreign Investment, investor perceptions, Earthquake, Analytical Hierarchy Process, Regression Test-MWD.